Interactive Tutorial for Introducing the Measurement Theory and Practice - Camero, R.; Zapata-Torres, M.; Calzadilla, O.; Ángeles, F. (Revista Cubana de Física; Vol 24 No 1 (2007): IV Ibero-American Workshop on Teaching of University Physics, 2007)
This work describes development of multimedia software to teaching measurement process of physical measures in middle high school. This material help teachers and students to develop the required capabilities for making right direct and indirect measurements, identifying possible errors sources and reporting values with uncertain. Software was designed with Macromedia Authorware and Macromedia Flash. This software includes measurement concepts which are explained using conceptual maps, lectures, images, pictures, videos and interactive learning activities. In Virtual lab section, there are some simulations to make virtual lab practices to determinate length with rules and vernier.